Additive Manufacturing Food: Technology and Materials - Ghazali, M.I.M.; Baharuddin A.S.; Alauddin M.S.; Dahlan, A.; Fuzi, S.F.Z.; Shaarani, S.M.; Hanafi, M.A. (Rynnye Lyan Resources, 2024)
Indexed by Scopus/MyCite